ANALISIS FREE CASH FLOW DAN PROFITABILITAS TERHADAP KEBIJAKAN HUTANG DENGAN INVESTMENT OPPORTUNITY SET - aditya Kurniawan (Prodi Magister Manajemen FE-UST, 2019)
This study aims to analyze the Free Cash Flow and Profitability toward debt policy with the Investments Opportunity Set as an Intervening variable (Empirical Study on Manufacturing Companies listed on the Indonesia Stock Exchange for the period 2012 to 2016). The population was 131 manufacturing companies trough the sampling technique used was purposive sampling and obtained a sample of 30 companies. The data analysis technique used is Descriptive and Partial Least Square (PLS) analysis. The results of this study indicate: Free cash flow does not affect the debt policy but Profitability affects the debt policy of manufacturing companies listed on the Indonesia Stock Exchange for the period 2012-2016. Free cash flow has an effect but Profitability does not affect on the Investment Opportunity Set for manufacturing companies listed on the Indonesia Stock Exchange for the period 2012-2016. The Investment Opportunity Set does not affect the debt policy of manufacturing companies listed on the Indonesia Stock Exchange for the period 2012-2016. Keywords: Free Cash Flow, Return On Investment, Investment Opportunity Set and Debt to Equity Ratio.